COVID-19 vaccination in Chinese children: a cross-sectional study on the cognition, psychological anxiety state and the willingness toward vaccination. Issue 1 (31st December 2022) - Yang, Jin; Zhang, Ting; Qi, Weiran; Zhang, Xingxing; Jia, Mengmeng; Leng, Zhiwei; Wang, Qing; Yang, Yuan; Yang, Weizhong; Ma, Libing; Feng, Luzhao; Wang, Chen
ABSTRACT: It is important to understand the cognition, willingness, and psychological anxiety state of Chinese guardians toward COVID-19 vaccination for their children to predict the future vaccination rate and to help the design of policies that aim to expand the population with immunity against COVID-19. This study collected data with a professional vaccination registration platform for children named "Xiao Dou Miao" in February 2021. The psychological anxiety state of the guardians was self-evaluated using the psychological anxiety scale. Factors that might influence the willingness of guardians to vaccinate their children were identified using logistic regression analysis. This study included 12, 872 questionnaires with 70.9% of guardians showing willingness to vaccinate their children. Guardians who were male, aged 40–49 and from rural area were more willing to vaccinate their children. Fathers, guardians with higher education and income, whose children have a history of adverse vaccine reactions and allergies were less willing to vaccinate their children ( p < .001). More than 80% of the guardians expressed a high level of trust for vaccine information released by official and health-related agencies. Guardians who were not vaccinated were more anxious than those who were vaccinated (χ2 = 27.99, p < .001). To protect children from COVID-19, vaccine coverage in children should be expanded rapidly and public awareness on vaccine safety and effectiveness should be improved.